Two new Nirvanini genera from China (Hemiptera: Cicadellidae) - Gao, Min; Dai, Wu; Zhang, Yalin (Zootaxa, 2014)
Two new Nirvanini genera, Decursusnirvana gen. nov. (type species: Decursusnirvana fasciiformis sp. nov.) and Sinonirvana gen. nov. (type species: Sinonirvana hirsuta sp. nov.), including two new species, D. fasciiformis sp. nov. and S. hirsuta, sp. nov. from China are described. One new combination, Decursusnirvana excelsa (Melichar) n. comb., is also proposed. Decursusnirvana most closely resembles Oniella Matsumura, but it may be distinguished from the latter by the aedeagus lacking an atrium and with the shaft with its basal half straight and apical half strongly curved ventrally, with a pair of processes. Sinonirvana gen. nov is similar to Decursusnirvana gen. nov., differs from the latter as follows: head more elongate with anteclypeus much broader and not extended beyond margin of gena. Also, the pygofer lobe is solid (not divided in two places like the latter) and the subgenital plate has numerous long, fine setae. Detailed morphological descriptions and illustrations of all three species are given and a key to all male species in two genera is also provided.